2011
DOI: 10.1038/npp.2011.268
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone in the Central Nucleus of the Amygdala Reduces Yohimbine Stress-Induced Reinstatement of Ethanol-Seeking

Abstract: Chronic ethanol exposure leads to dysregulation of the hypothalamic-pituitary-adrenal axis, leading to changes in glucocorticoid release and function that have been proposed to maintain pathological alcohol consumption and increase vulnerability to relapse during abstinence. The objective of this study was to determine whether mifepristone, a glucocorticoid receptor antagonist, plays a role in ethanol self-administration and reinstatement. Male, Long-Evans rats were trained to self-administer either ethanol or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
80
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 96 publications
11
80
0
Order By: Relevance
“…Mifepristone (n = 5/group; dose × group interaction: F 2,16 = 4.044, P = 0.0379) at 10 μg/side (P = 0.0068) and 30 μg/side (P = 0.0280), significantly and specifically reduced alcohol intake in dependent rats, when compared with vehicle (0 μg/side) controls ( Figure 1D). Our demonstration of increased GR phosphorylation during dependence and reduction of compulsive-like alcohol drinking by intra-CeA mifepristone injection, combined with previous findings (19), indicate that increased GR signaling in the CeA plays a functional role in alcohol drinking and seeking.…”
Section: Resultssupporting
confidence: 80%
“…Mifepristone (n = 5/group; dose × group interaction: F 2,16 = 4.044, P = 0.0379) at 10 μg/side (P = 0.0068) and 30 μg/side (P = 0.0280), significantly and specifically reduced alcohol intake in dependent rats, when compared with vehicle (0 μg/side) controls ( Figure 1D). Our demonstration of increased GR phosphorylation during dependence and reduction of compulsive-like alcohol drinking by intra-CeA mifepristone injection, combined with previous findings (19), indicate that increased GR signaling in the CeA plays a functional role in alcohol drinking and seeking.…”
Section: Resultssupporting
confidence: 80%
“…Gabapentin reduced both the anxiogenic-like behavior and the increased ethanol self-administration observed in withdrawn, ethanol dependent rats, but not non-dependent rats (Roberto et al 2008; Besheer et al 2016; Watson et al 1997) and was found to improve emotional function and reduce insomnia and alcohol use in abstinent alcoholics (Bonnet et al 2007; Malcolm et al 2007; Brower et al 2008; Myrick et al 2009; Mason et al 2014). Most recently, the glucocorticoid receptor antagonist mifepristone, which like CRF 1 antagonists more efficaciously reduces ethanol intake in dependent rodents during abstinence than in non-dependent rodents (Yang et al 2008; Simms et al 2012; Vendruscolo et al 2012; Vendruscolo et al 2015), was found to reduce alcohol-cued craving in the laboratory as well as naturalistic measures of alcohol use in a double-blind, placebo-controlled study of 56 alcohol-dependent human subjects (NCT01548417; Vendruscolo et al 2015). Thus, the preclinical models do show predictive sensitivity to detect effective treatments.…”
Section: Performance In Animal Modelsmentioning
confidence: 99%
“…The glucocorticoid receptor antagonist mefipristone is a promising therapeutic, which when administered systemically or locally into the central amygdala (CeA), reduced yohimbine-stress induced reinstatement of ethanol seeking in male Long-Evans rats (Simms et al, 2012) and when given systemically reduced alcohol self-administration in alcohol dependent Wistar rats (Vendruscolo et al, 2015). In a recent study, mefipristone reduced alcohol-cued craving and self-reported alcohol consumption in 56 alcohol-dependent, outpatient human volunteers who had been abstinent for 3 days before the alcohol cue laboratory session (Vendruscolo et al, 2015).…”
Section: Resultsmentioning
confidence: 99%